"Will you hear my voice?": to engage older patients online, listen to them about their lives offline - Michael L. Millenson (BMC, 2020)
Abstract The scope of health information and health care services available online is rapidly expanding. At the same time, COVID-19 is causing vulnerable elders to reconsider in-person provider visits. In that context, recently published research by Y. Mizrachi et al. examining obstacles to the use of online health services (OHS) among adults age 50 and up takes on new importance. An iconic Israeli song begins, "Will you hear my voice?" (Hebrew Songs. Zemer Nugeh (Hatishmah Koli), 2020). What makes Mizrachi et al.'s findings particularly intriguing, despite several caveats, is the manner in which they demonstrated a commitment to genuinely listen to individual voices. The researchers spoke "openly and bluntly" with interviewees as peers and were rewarded with "specific, well-defined and applicable answers with the potential to be used." The most striking findings came in candid answers that went beyond the factors intrinsic to the online offerings and addressed important factors in what regular Internet users often refer to as IRL ("in real life"), such as support from family. The necessity of avoiding preconceptions about the most effective manner to engage patients underscores the importance of patient and family advisory councils (PFACs). PFACs, increasingly being adopted by health care organizations globally, provide an ongoing ability to listen and respond to the "patient voice." Effectively addressing obstacles to older adults' use of the full range of online health resources will require the involvement not just of health plans and government, but also of voluntary organizations, providers, families and others integral to users' offline "real lives." Sustained, focused listening must be a central part of that effort.